2014
DOI: 10.1038/modpathol.2013.249
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker evaluation of face transplant rejection: association of donor T cells with target cell injury

Abstract: This series of 113 sequential biopsies of full facial transplants provides findings of potential translational significance as well as biological insights that could prompt reexamination of conventional paradigms of effector pathways in skin allograft rejection. Serial biopsies before, during, and after rejection episodes were evaluated for clinicopathological assessment that in selected cases included specific biomarkers for donorversus-recipient T cells. Histologic evidence of rejection included lymphocyte-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 46 publications
(57 reference statements)
2
75
0
Order By: Relevance
“…CD8 + T‐cells mediate epidermal involvement, with the CD4 + subtype mainly associated with dermal interactions. These T‐cell populations are presumed to originate from the recipient and have the ability to cause injury to epidermal and dermal microvascular target cells (Lian et al, ). Our IHC study demonstrated the clinical rejection status decreased after application of topical immunosuppressant drugs, which correlated with T cell expressions.…”
Section: Discussionmentioning
confidence: 99%
“…CD8 + T‐cells mediate epidermal involvement, with the CD4 + subtype mainly associated with dermal interactions. These T‐cell populations are presumed to originate from the recipient and have the ability to cause injury to epidermal and dermal microvascular target cells (Lian et al, ). Our IHC study demonstrated the clinical rejection status decreased after application of topical immunosuppressant drugs, which correlated with T cell expressions.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study published recently by Lian et al . demonstrates this may not be the case in VCA allografts. The finding by Clark et al .…”
Section: Tissue Components Of Composite Allograftsmentioning
confidence: 92%
“…that normal skin contains twice as many T effector cells as in the peripheral blood suggests that the donor skin should be home to many donor T cells, even after the transplant. In a study of 113 biopsies from face transplant recipients, during active rejection, the majority of the lymphocytes spatially associated with areas of injury were of donor rather than recipient origin . Additionally, most of these donor lymphocytes are CD8+, and of a T resident memory (T RM ) phenotype.…”
Section: Tissue Components Of Composite Allograftsmentioning
confidence: 99%
“…Recipient blood vessels clearly can and do present donor peptide in MHC, which allo-specific T cells recognize, infiltrate and trigger CMR. VCA are also found to contain numerous, possibly expanded populations of donor T cells (16, 36, 37). Whether donor-derived T cells attack blood vessels of recipient origin that grow into VCA is unknown, but a question of potential import since donor T cells presumably are less subject to control by induction regimens.…”
Section: The Origin Of the Vascular Supplymentioning
confidence: 99%